Analysis of the social discourse on COVID-19 in the Spanish digital media - Rivas Rebaque, Begoña; Gertrudix, Manuel; Chihuailaf, Andres; Carbonell-Alcocer, Alejandro; Romero-Luis, Juan; Sanchez-Acedo, Alberto (Revista Española de Comunicación en Salud, 2024)
Introduction: The media and social media have informed the public about the details and the evolution of the COVID-19 pandemic and the subsequent prevalence of Long COVID. There has been growing concern throughout that information should be accurate, sufficient, and truthful. Objective: The aim of this research is to identify this discourse in the Spanish digital media world in order to understand the media representations they produce and to improve communication awareness campaigns. Methods: Adopting a threefold methodological approach (Social Medial Listening, discourse analysis and social representation), the media discourse of Long COVID on different social media and in Spanish digital media is analysed for 12 months using the DIGIMIND tool. The five components of Laswell’s Model of Communication: who; (says) what; (to) whom, which (channel) and what (effect), are evaluated and reported. Results: The analysis shows, among other results, which keywords are most present in social media and in digital press; the most consulted sources of information; or how information links are established between those studied. Conclusions: Based on these findings, an effective communication guide on Long COVID has been developed with a set of recommendations to be implemented by government agencies, health communication specialists and affected groups.
Keywords: Discourse Analysis; Mass Media; Coronavirus; Long COVID; Digimind Software; Health Communication